National Pharmaceutical Assistance Policy in the Brazilian Unified Health System (SUS): Between Social Achievements and Structural Challenges (REMUNOM, 2025)
The National Pharmaceutical Assistance Policy (PNAF), established as one of the pillars of the Unified Health System (SUS), represents a fundamental achievement for society in realizing the right to health in Brazil. This article aims to evaluate the social reach of the PNAF, analyzing its achievements, limitations, and future challenges. Methodologically, it is a dissertation-argumentative analysis based on current scientific evidence. The PNAF, grounded in the principles of universality, comprehensiveness, and equity, has promoted significant advances in democratizing access to medicines, especially through programs such as the Popular Pharmacy program and integration with Primary Health Care. The creation of the National List of Essential Medicines (RENAME) ensured transparency and standardization; however, its implementation faces structural obstacles, such as regional disparities in management, fragmentation of policies, and economic pressures resulting from technological dependence and the high costs of medicines. The judicialization of healthcare and issues related to transparency in the incorporation of technologies by CONITEC compromise financial sustainability and collective planning. As perspectives for strengthening the National Pharmaceutical Assistance Policy (PNAF), it is proposed to improve intersectoral governance, invest in public drug production, and expand social participation. Furthermore, the incorporation of new technologies, such as Artificial Intelligence, emerges as a promising tool to optimize inventory management, pharmacovigilance, and support clinical decision-making. It is concluded that, despite the advances, the consolidation of an equitable and efficient PNAF requires a continuous commitment to overcoming its historical limitations and adopting innovative strategies that strengthen the Brazilian Unified Health System (SUS).